FACTORS AFFECTING THE USE OF PAYLATER AND ITS EFFECT ON FINANCIAL WELL-BEING - Karlina Ayu Putri Dhahana; Maria Ulpah (Sean Institute, 2023)
Paylater is an installment credit service and is included in the fintech payment sector. Currently, Paylater has become a trend because it allows consumers to make purchases in installments and pay for them in the future and is easily accessible to anyone. However, in reality, the ease of access and trust in fintech products not only provide benefits but also bring people's tendency to go into debt. Therefore, the purpose of this study is to find out the factors that influence a person to use Paylater and how it impacts the financial well-being of users of the feature. This research is a quantitative study where the data used in this study is primary data covering 355 respondents. Data processing is carried out with a Structural Equation Modeling (SEM) model to estimate the relationship between variables. The results showed that Performance Expectancy, Facilitating Condition and Financial Literacy had a significant positive impact on the Adoption of Paylater. In addition, it can be seen that Adoption of Paylater can mediate the influence of Performance Expectancy, Social Influence, Facilitating Conditions negatively and significantly on Financial Well-being while Financial Literacy can provide positive and significant to Financial Well-being. However, there was no significant influence of Social Influence dah Habit on Adoption of Paylater and Habit on Financial Well-being.